Selecting the optimal energy mix and sizing of a isolated microgrid - Muñoz, Yecid; Ospino, Adalberto (UNIVERSIDAD ANTONIO NARIÑO, 2013)
This paper presents a procedure resulting from a research that analyzed the strategies for energy supply and consumption criteria in order to get a optimal microgrid technically and economically. Is shown how the method was applied in a an isolated area in Necocli - Colombia, for which was obtained data on energy consumption and availability of renewable energy resources, supplied by the Planning Institute of IPSE energy solutions, responsible for energy supply to remote country areas